La función abstractiva como distintivo básico de la inteligencia humana - Guzmán Vicente Burgoa, Lorenzo de ca. 21. Jh. (Sapientia, 2018)
The clear, not only gradual but specific distinction between sensitive knowledge and intellectual knowledge, is a topic that has been discussed since ancient times. For my part, I hold the specific difference of such functions, excluding, however, the substantial anthropological dualism of mindbody. On the other hand, the basic radical or distinctive character of higher intellective functions is also being discussed: in this paper we argue, after facing various opinions, that it is found in the ability to exercise formal abstraction, as an evolutionary achievement of the human mind and even partial liberation of matter and sensitivity.